2014
DOI: 10.1002/anie.201409289
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Accelerated Formation of Chiral, Optically Active Buta‐1,3‐dienes

Abstract: The formal [2+2] cycloaddition-retroelectrocyclization (CA-RE) reactions between tetracyanoethylene (TCNE) and strained, electron-rich dibenzo-fused cyclooctynes were studied. The effect of ring strain on the reaction kinetics was quantified, revealing that the rates of cycloaddition using strained, cyclic alkynes are up to 5500 times greater at 298 K than those of reactions using unstrained alkynes. Cyclobutene reaction intermediates, as well as buta-1,3-diene products, were isolated and their structures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 73 publications
0
19
3
2
Order By: Relevance
“…In contrast to previous studies using dibenzo-fused cyclooctynes,r eported by Diederich et al, [17] for our macrocyclic alkynes ac yclobutene intermediate was not observed, suggesting the second-order CA (2 + TCNE ! Theb uilt-in alkyne curvature rationalizes the experimental observation that the reaction occurs at 0 8 8Cf or the highly strained 1,w hile the larger macrocycles do not react under these conditions.Although the predicted enthalpic barrier for the RC step is actually higher than for the CA step,the latter is predicted to be rate-determining overall because of the large entropic contribution, which is in good qualitative agreement with our experimental observations.T his unique mode of reactivity is in contrast to the strained cyclooctynes reported by Diederich et al, [17] where the RC step is rate determining.Wespeculate that this difference can be ascribed to the rotational flexibility of the phenyl rings in macrocycle 1-3,w hich, unlike the rigid scaffold of dibenzo-fused cyclooctynes,a llows them to accommodate the steric repulsion between the aryl À Ha nd the dicyanovinyl groups during the cyclobutene ring opening in the RC step,a nd thus lower the corresponding reaction barrier (TS2). 18).…”
Section: Angewandte Chemiecontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previous studies using dibenzo-fused cyclooctynes,r eported by Diederich et al, [17] for our macrocyclic alkynes ac yclobutene intermediate was not observed, suggesting the second-order CA (2 + TCNE ! Theb uilt-in alkyne curvature rationalizes the experimental observation that the reaction occurs at 0 8 8Cf or the highly strained 1,w hile the larger macrocycles do not react under these conditions.Although the predicted enthalpic barrier for the RC step is actually higher than for the CA step,the latter is predicted to be rate-determining overall because of the large entropic contribution, which is in good qualitative agreement with our experimental observations.T his unique mode of reactivity is in contrast to the strained cyclooctynes reported by Diederich et al, [17] where the RC step is rate determining.Wespeculate that this difference can be ascribed to the rotational flexibility of the phenyl rings in macrocycle 1-3,w hich, unlike the rigid scaffold of dibenzo-fused cyclooctynes,a llows them to accommodate the steric repulsion between the aryl À Ha nd the dicyanovinyl groups during the cyclobutene ring opening in the RC step,a nd thus lower the corresponding reaction barrier (TS2). 18).…”
Section: Angewandte Chemiecontrasting
confidence: 99%
“…The moderate yields for 17 (59 %) and 19 (68 %) are ascribed to the limited stability of the starting materials 1 and 3 under the reaction conditions,r espectively.I nc ontrast, compound 2 (97 %y ield) appears to represent af avorable trade-off between stability and reactivity of the internal alkyne unit that allowed for kinetic studies.The reaction of 2 with TCNE was monitored by 1 HNMR spectroscopy at various temperatures and the kinetic data were subjected to Eyring analysis (Supporting Information). In contrast to previous studies using dibenzo-fused cyclooctynes,r eported by Diederich et al, [17] for our macrocyclic alkynes ac yclobutene intermediate was not observed, suggesting the second-order CA (2 + TCNE ! 20)isthe rate-determining step followed by rapid first-order RC ring opening (20 !…”
Section: Angewandte Chemiecontrasting
confidence: 99%
See 1 more Smart Citation
“…[74] The effect of ring strain on the CA-RE reaction between electronrich strained cycloalkynes and TCNE was studied. [75] The…”
Section: Complex Chromophoric Systemsmentioning
confidence: 99%
“…Hence, structurally modified versions of the cyclooctyne scaffold, such as DIFO, DIBO, and DIBAC (Figure ), emerged as promising tools for bioorthogonal chemistry after cyclooctynes were shown to undergo SPAAC reactions in biological media . In the context of click chemistry, another appealing conversion is represented by the [2+2]cycloaddition–retrocyclization (CA‐RC) reaction of strained alkynes with an electron‐deficient alkene, such as tetracyanoethylene (TCNE) . This strategy enables rapid access to nonplanar donor–acceptor chromophores based on molecular and polymeric scaffolds, which feature a range of attractive properties, such as intramolecular charge‐transfer bands, nonlinear optical properties, and pronounced redox activity .…”
Section: Figurementioning
confidence: 99%